Management of Human Bites of “Face” - Mita Prasanna (Indian Journal of Plastic Surgery)
In literature human bite of the hand has received more attention than that of face. The treatment of the human bite wounds at the two sites differ. Highlighting the reasons, the principles of management of human bites of ‘Face’ are discussed. Representative cases are reported.